Scenario of Hooch Tragedy in Gujarat State - Prajapati, Pankaj; Govekar, Ganesh; Pathak , Akhilesh (Journal of Indian Academy of Forensic Medicine, 2012)
Currently, the Hooch Tragedy occurred in July 2009 at Ahmedabad, Gujarat, resulting in the  death of 136 people from consumption of bootlegged liquor. This was the highest death toll in Gujarat  from consuming moonshine since 1989 when 132 people had died in a matter of days in Vadodara. The  number of patients admitted in the four hospitals of Ahmedabad-Civil Hospital, V.S. Hospital, LG Hospital  and Shardaben Hospital had risen to 276 with nearly 100 needing observation either in ICUs or surgical  wards. Embarrassed by the scale of the tragedy in a state where consumption and sale of liquor is  officially banned, police swept through Gujarat in search of those, illegally selling home-made liquor.  Gujarat is the country's only state where sale and consumption of liquor is banned in deference to  Mahatma Gandhi, a Gujarati who was passionately opposed to liquor. This has led to a proliferation of  illegal liquor dens, whose home-made brew is mostly consumed by those from low income families who  can't afford high priced drinks available outside the state.
Keywords: Hooch Tragedy; Moonshine Tragedy; Liquor; Brew